Distinct and complex bacterial profiles in human periodontitis and health revealed by 16S pyrosequencing - Griffen, Ann L; Beall, Clifford J; Campbell, James H; Firestone, Noah D; Kumar, Purnima S; Yang, Zamin K; Podar, Mircea; Leys, Eugene J (The ISME Journal, 2012)
Periodontitis has a polymicrobial etiology within the framework of a complex microbial ecosystem. With advances in sequencing technologies, comprehensive studies to elucidate bacterial community differences have recently become possible. We used 454 sequencing of 16S rRNA genes to compare subgingival bacterial communities from 29 periodontally healthy controls and 29 subjects with chronic periodontitis. Amplicons from both the V1-2 and V4 regions of the 16S gene were sequenced, yielding 1 393 579 sequences. They were identified by BLAST against a curated oral 16S database, and mapped to 16 phyla, 106 genera, and 596 species. 81% of sequences could be mapped to cultivated species. Differences between health- and periodontitis-associated bacterial communities were observed at all phylogenetic levels, and UniFrac and principal coordinates analysis showed distinct community profiles in health and disease. Community diversity was higher in disease, and 123 species were identified that were significantly more abundant in disease, and 53 in health. Spirochaetes , Synergistetes and Bacteroidetes were more abundant in disease, whereas the Proteobacteria were found at higher levels in healthy controls. Within the phylum Firmicutes, the class Bacilli was health-associated, whereas the Clostridia , Negativicutes and Erysipelotrichia were associated with disease. These results implicate a number of taxa that will be targets for future research. Some, such as Filifactor alocis and many Spirochetes were represented by a large fraction of sequences as compared with previously identified targets. Elucidation of these differences in community composition provides a basis for further understanding the pathogenesis of periodontitis.